The Impact of a Multi-faceted Mentoring Program on Student-Led Micro-Enterprises: An Analysis of Revenue Growth and Managerial Transformation - Suryani, Pesi; Puspitasari, Nindya Farah Dwi; Daurrohmah, Eka Wirajuang; Gaol, Lasando Lumban; Robiansyah, Anton; Oktari, Vivi; Hadiwidjaja, Rini Dwiyani; Rahmawati, Seli; Pramesti, Kyeszhya Arnellita; Al Rasyid, Muhamad Harun (Media Publikasi Cendekia Indonesia, 2025)
This community service program, implemented using a Participatory Action Research (PAR) approach, aims to assist students in developing their micro-enterprises to become more professional, efficient, and sustainable. The program responds to the challenges faced by student entrepreneurs, ranging from business management and marketing to product development. Implementation methods included participatory needs identification, provision of targeted resources, tailored training in business management and digital marketing, infrastructure enhancement, and ongoing participatory evaluation. The results demonstrate significant progress among the three mentored student businesses. Ayam Geprek Bunda increased sales by 100% through facility upgrades and online marketing strategies. The Beaded Handicrafts business recorded a 233% revenue growth after design innovation and digital marketing initiatives. Meanwhile, Peyek Bude achieved a 35% sales increase through community-based marketing strategies and improved packaging quality. This program has proven effective in enhancing managerial capacity, business income, and awareness of professional business practices. The findings underscore the importance of sustained entrepreneurial mentoring within campus environments as a strategy to empower students, while fostering positive social impact through the emergence of young, inspirational leaders in entrepreneurship.